Impact of Chronic Kidney Disease on Outcomes in Cirrhosis. Issue 6 (25th April 2019) - Wong, Florence; Reddy, K. Rajender; O'Leary, Jacqueline G.; Tandon, Puneeta; Biggins, Scott W.; Garcia‐Tsao, Guadalupe; Maliakkal, Benedict J.; Lai, Jennifer C.; Fallon, Michael B.; Vargas, Hugo E.; Subramanian, Ram; Thuluvath, Paul J.; et al.
Abstract : We hypothesize that the prevalence of chronic kidney disease (CKD) among patients with cirrhosis has increased due to the increased prevalence of CKD‐associated comorbidities, such as diabetes. We aimed to assess the characteristics of hospitalized patients with cirrhosis with CKD and its impact on renal and patient outcomes. The North American Consortium for the Study of End‐Stage Liver Disease (NACSELD) prospectively enrolled nonelectively admitted patients with cirrhosis and collected data on demographics, laboratory results, in‐hospital clinical course, and postdischarge 3‐month outcomes. CKD positive (CKD+) patients, defined as having an estimated glomerular filtration rate (eGFR; Modification of Diet in Renal Disease–4 variable formula) of ≤60 mL/minute for >3 months, were compared with chronic kidney disease negative (CKD–) patients for development of organ failures, hospital course, and survival. There were 1099 CKD+ patients (46.8% of 2346 enrolled patients) who had significantly higher serum creatinine (2.21 ± 1.33 versus 0.83 ± 0.21 mg/dL in the CKD– group) on admission, higher prevalence of nonalcoholic steatohepatitis cirrhosis etiology, diabetes, refractory ascites, and hospital admissions in the previous 6 months compared with the CKD– group (all P  < 0.001). Propensity matching (n = 922 in each group) by Child‐Pugh scores (9.78 ± 2.05 versus 9.74 ± 2.04, P  = 0.70) showed that CKD+ patients had significantly higher rates of superimposed acute kidney injury (AKI; 68% versus 21%; P  < 0.001) and eventual need for dialysis (11% versus 2%; P  < 0.001) than CKD– patients. CKD+ patients also had more cases of acute‐on‐chronic liver failure as defined by the NACSELD group, which was associated with reduced 30‐ and 90‐day overall survival ( P  < 0.001 for both). A 10 mL/minute drop in eGFR was associated with a 13.1% increase in the risk of 30‐day mortality. In conclusion, patients with CKD should be treated as a high‐risk group among hospitalized patients with cirrhosis due to their poor survival, and they should be monitored carefully for the development of superimposed AKI.